Influência do processamento no comportamento mecânico de nanocompósitos de poliamida 6 com nanosílica - Queiroz, Breno Dutra de (2015)
In this study nanocomposites of polyamide-6 (PA-6) reinforced with silica nanoparticles (SiO2) were prepared in order to promote improved mechanical properties for engineering applications. The nanoparticles’ surfaces were chemically modified with the silane agent 3-aminopropyltrimethoxysilane (3- APTMS) to improve the chemical and physical interactions between them and the PA-6 matrix. Nuclear magnetic resonance analysis (NMR) and Fourier transform infrared absorption spectroscopy (FT-IR) showed that 3-APTMS grafting on nanoparticles surface was accomplished. The nanocomposites mixing process was studied in two forms: by torque rheometry, using a torque rheometer internal mixer; and in a co-rotating and intermeshing twin-screw extruder. A preliminary study of the influence of processing variables at the torque rheometer on the degradation of polyamide-6 matrix was performed. The results showed that the greater the filling volume of the mixture in the chamber and the rotational speed of the rheometer’s rotors, the lower the degradation of the polyamide-6. Based on this preliminary study, compositions with 1, 2, and 4 % weight of SiO2 nanoparticles, both unmodified and chemically modified with 3-APTMS were prepared in the torque rheometer. The nanocomposites were compression molded and it was observed that nanocomposites reinforced with 1 wt.% SiO2, both unmodified and surface-modified, presented the best tensile properties. For the nanocomposite samples processed in the twin-screw extruder, the influence of relevant variables – nanoparticle content, chemical surface modification, physical form of the fed PA-6 (granule and powder), rotational speed of screws and extruder feed rate – on mechanical, thermal, and dynamic-mechanical properties were studied. The samples were afterwards injection molded and it was observed that the samples produced using 1 wt.% surface-modified and 100% finely ground PA-6 showed the higher tensile modulus and yield strength values.